Patients With Chronic Spinal Pain Benefit From Pain Neuroscience Education Regardless the Self‐Reported Signs of Central Sensitization: Secondary Analysis of a Randomized Controlled Multicenter Trial. Issue 12 (1st December 2018) - Malfliet, Anneleen; Kregel, Jeroen; Meeus, Mira; Danneels, Lieven; Cagnie, Barbara; Roussel, Nathalie; Nijs, Jo
Abstract: Background: Pain neuroscience education is effective in chronic pain management. Central sensitization (ie, generalized hypersensitivity) is often explained as the underlying mechanism for chronic pain, because of its clinical relevance and influence on pain severity, prognosis, and treatment outcome. Objectives: To examine whether patients with more or fewer symptoms of central sensitization respond differently to pain neuroscience education. Design: A secondary analysis of a multicenter, triple‐blind randomized controlled trial. Setting: University Hospital Ghent and University Hospital Brussels, Belgium. Patients: 120 persons with chronic spinal pain with high or low self‐reported symptoms of central sensitization. Interventions: Pain neuroscience education or neck/back school. Both interventions were delivered in 3 sessions: 1 group session, 1 online session, and 1 individual session. Main Outcome Measures: disability (primary), pain catastrophizing, kinesiophobia, illness perceptions, and hypervigilance. Results: Pain disability did not change in any group ( P = .242). Regarding secondary outcomes: significant interaction effects were found for pain catastrophizing ( P ‐values: P = .02 to P = .05), kinesiophobia ( P = .02), and several aspects of illness perceptions (chronicity: P = .002; negative consequences: P = .02; personal control: P = .02; and cyclicity: P = .02). Bonferroni post hoc analysis showed that only the pain neuroscience education group (high and low self‐reported symptoms of central sensitization) showed a significant improvement regarding kinesiophobia ( P  < .001, medium effect sizes), perceived negative consequence ( P = .004 and P < .001, small to medium effect sizes), and perceived cyclicity of the illness ( P = .01 and P = .01, small effect sizes). Pain catastrophizing only significantly reduced in people with high self‐reported central sensitization symptoms ( P < .05). Conclusion: Pain neuroscience education is useful in all patients with chronic spinal pain as it improves kinesiophobia and the perceived negative consequences and cyclicity of the illness regardless the self‐reported signs of central sensitization. Regarding pain catastrophizing, pain neuroscience education is more effective in patients with high self‐reported symptoms of central sensitization. Level of Evidence: I